2022
DOI: 10.1101/2022.06.09.495361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacteriophage anti-defense genes that neutralize TIR and STING immune responses

Abstract: Programmed cell suicide of infected bacteria, known as abortive infection (Abi), serves as a central immune defense strategy to prevent the spread of bacteriophage viruses and other invasive genetic elements across a population. Many Abi systems utilize bespoke cyclic nucleotide immune messengers generated upon infection to rapidly mobilize cognate death effectors. Here, we identify a large family of bacteriophage nucleotidyltransferases (NTases) that synthesize competitor cyclic dinucleotide (CDN) ligands, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Critically, this has been recently shown with Pectobacterium spp. phage PcCB7V, which encodes the nucleotide pyrophosphatase MazG that is enriched against TIR-STING anti-phage systems and reduces (p)ppGpp 14 . In addition, these authors demonstrated that (p)ppGpp is increased during phage attack 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Critically, this has been recently shown with Pectobacterium spp. phage PcCB7V, which encodes the nucleotide pyrophosphatase MazG that is enriched against TIR-STING anti-phage systems and reduces (p)ppGpp 14 . In addition, these authors demonstrated that (p)ppGpp is increased during phage attack 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Acrs were detected using AcrFinder 40 . For the detection of anti-RM ( ardA 37 , klcA 38 , ardB, ocyA, ocr, darA, darB 39 , anti-CBASS Type I ( acb1 ) 41 , anti-CBASS Type II ( acbII ) 27 , anti-Pycsar ( apyc ) 41 and anti-TIR-STING 42 genes, we first searched for P. aeruginosa homologs using PSI-BLAST 66 (maximum of 3 runs with 500 sequences; coverage > 60%, pident > 10%). Homolog functionality was checked using HMMer 67 and HHpred 68 .…”
Section: Methodsmentioning
confidence: 99%
“…To assess the impact of phage-encoded anti-defenses in the phage infectivity profile of the clinical strains, we searched for known anti-defenses in the phage genomes, including anti-RM [37][38][39] , Acr 40 , anti-CBASS 27,41 , anti-Pycsar 41 , and anti-TIR-STING 42 proteins. Only one antidefense gene, anti-CBASS Type II (acbII) was found, in phage ϕPa48.…”
Section: Infectivity Profiles Of the Clinical Strains Correspond To S...mentioning
confidence: 99%
“…For example, the co-occurrence of a Type I BREX and Type IV RM systems prevents the emergence of epigenetic mutants that overcome BREX, since these are cleaved by the Type IV RM system 24 , and the co-existence of RM and CRISPR-Cas leads to a reduction in the frequency of spontaneous phage mutants that escape both defences as well as a higher rate of CRISPR immunity acquisition 25,26,27 . However, many phage can employ more sophisticated counter-defence mechanisms, such as anti-RM 5 , anti-CRISPR (Acr) 6 and the more recently identified anti-CBASS 7,8 , anti-Pycsar 8 and anti-TIR-STING 9 proteins. We currently lack an understanding of how multi-layered bacterial defences impact the efficacy and deployment of these sophisticated phage counter-defence systems, and how this influences bacteria-phage coevolution.…”
Section: Introductionmentioning
confidence: 99%
“…
The constant arms race between bacteria and their phages has resulted in a large diversity of bacterial defence systems 1,2 , with many bacteria carrying several systems 3,4 . In response, phages often carry counter-defence genes [5][6][7][8][9] . If and how bacterial defence mechanisms interact to protect against phages with counter-defence genes remains unclear.
…”
mentioning
confidence: 99%